SAT0177 Safety events are similar with abatacept vs placebo treatment in ra: results from integrated data analysis from nine clinical trials. (15th June 2017) - Soule, B; Hochberg, M; Fleming, D; Torbeyns, A; Simon, T; Banerjee, S; Boers, M
Abstract : Background: Abatacept is a selective co-stimulation modulator that consists of the extracellular domain of human cytotoxic T lymphocyte-associated antigen-4 linked to the modified Fc portion of human immunoglobulin and was approved initially for the treatment of RA in 2005. The integrated safety database for abatacept in adult RA comprises data from short- and long-term periods of 16 open-label and double-blind RA clinical trials, and combines studies of both IV and SC abatacept involving 7044 total patients. Of these, data from the 9 double-blind, placebo-controlled studies involving 4138 total patients were included in this analysis. The most recent overall safety analysis was performed in 2012 and reported IV and SC results separately. Objectives: To provide an update of the overall abatacept safety profile based on data analysis from both IV and SC trials. Methods: This evaluation included all patients with RA enrolled in 9 key double-blind, placebo-controlled clinical trials of IV and/or SC abatacept. The safety analysis includes all serious adverse events (SAEs), as well as AEs of interest including infections, malignancies and autoimmune diseases. Results: In total, 2653 patients were exposed to abatacept and 1485 received placebo. During the double-blind, controlled period, the mean (SD) duration of exposure was 10.3 (3.5) months for the placebo group and 10.8 (3.3) months for the abatacept group for a total exposure of 2357 and 1254 patient years, respectively (Table 1 ). The proportion of patients as well as incidence rates for death, SAEs, infections, malignancy and autoimmune diseases were similar between those treated with abatacept and placebo (Table 2 ). Conclusions: In a large RA clinical trial database, safety events including deaths, serious infections, opportunistic infections, malignancies and autoimmune diseases occurred at similar frequencies and rates in the abatacept and placebo treatment groups. Disclosure of Interest: B. Soule Employee of: Bristol-Myers Squibb, M. Hochberg Shareholder of: Theralogix LLC, Grant/research support from: NIH, Consultant for: Bristol-Myers Squibb, EMD Serono Inc., Genentech/Roche, Novartis Pharma AG, Pfizer Inc, UCB Inc., D. Fleming Employee of: Bristol-Myers Squibb, A. Torbeyns Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, T. Simon Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, S. Banerjee Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, M. Boers Consultant for: Bristol-Myers Squibb